2022
DOI: 10.1002/ctm2.806
|View full text |Cite
|
Sign up to set email alerts
|

PI3K‐α/mTOR/BRD4 inhibitor alone or in combination with other anti‐virals blocks replication of SARS‐CoV‐2 and its variants of concern including Delta and Omicron

Abstract: Dear Editor, We demonstrated that SF2523, a dual small molecule inhibitor of PI3K-α/mTOR/BRD4 pathways, can inhibit the replication of SARS-CoV-2 and its emerging variants of concern (VOCs), including Delta and Omicron. Further, we also found that SF2523 acts synergistically with remdesivir (RDV) and MU-UNMC-2 (a small molecule entry inhibitor of SARS-CoV-2). 1 The ongoing COVID-19 pandemic due to the emergence of a novel coronavirus SARS-CoV-2 remains a significant health concern globally. Several vaccine can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…BRD4 is known to mediate immune and inflammatory responses to viral infection and was recently reported to regulate COVID-19-mediated cytokine storm and cardiac damage ( Mills et al., 2021 ). Furthermore, BET inhibitors were shown to downregulate the expression of viral host entry factors, such as angiotensin-converting enzyme 2 (ACE2), thereby limiting SARS-CoV-2 replication in vitro ( Gilham et al., 2021 ; Qiao et al., 2020 ), and have potent anti-viral activity ( Acharya et al., 2022 ; Qiao et al., 2020 ; Samelson et al., 2022 ). To examine the importance of the BRD4-E interaction for the SARS-CoV-2 life cycle, we infected the human lung bronchial epithelial cell line Calu-3 with a Delta variant of SARS-CoV-2 (pangolin linage B.1.617.2) and monitored infection by immunofluorescence ( Figures 4 A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…BRD4 is known to mediate immune and inflammatory responses to viral infection and was recently reported to regulate COVID-19-mediated cytokine storm and cardiac damage ( Mills et al., 2021 ). Furthermore, BET inhibitors were shown to downregulate the expression of viral host entry factors, such as angiotensin-converting enzyme 2 (ACE2), thereby limiting SARS-CoV-2 replication in vitro ( Gilham et al., 2021 ; Qiao et al., 2020 ), and have potent anti-viral activity ( Acharya et al., 2022 ; Qiao et al., 2020 ; Samelson et al., 2022 ). To examine the importance of the BRD4-E interaction for the SARS-CoV-2 life cycle, we infected the human lung bronchial epithelial cell line Calu-3 with a Delta variant of SARS-CoV-2 (pangolin linage B.1.617.2) and monitored infection by immunofluorescence ( Figures 4 A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed in vitro efficacy of SF2523 as a monotherapy and combined with remdesivir (RDV) or the newly developed inhibitor MU‐UNMC‐2. We found that SF2523, an inhibitor of PI3K‐α/mTOR/BRD4, effectively blocks the replication of SARS‐CoV‐2 and its VOCs, including delta and omicron 15 . Furthermore, SF2523 acts in synergy with the antiviral drug RDV and MU‐UNMC‐2, a small molecule inhibitor that blocks the entry of SARS‐CoV‐2 18 .…”
Section: Figurementioning
confidence: 88%
“…LARP1 downregulation by mTOR inhibitors blocks MERS virus replication and has an immunosuppressive function 14 . We have shown that BRD2/BRD4 and mTOR are critical host factors responsible for the pathogenesis of SARS‐CoV‐2 based on the activity of the small molecule SF2523 15 . SF2523 is a potent inhibitor of PI3Kα (IC 50 = 34 nM), PI3Kγ (IC 50 = 158 nM), DNA‐PK (IC 50 = 9 nM), BRD4 (IC 50 = 241 nM), and mTOR (IC 50 = 280 nM).…”
Section: Figurementioning
confidence: 99%
“…As this demographic often faces decreased vaccine-provided immunity, coronavirus disease 2019 treatments must be developed. We discuss a recent study by Acharya et al (2022) that found that SF2523 induced autophagy, reducing SARS-CoV-2 replication. Furthermore, across varying dosages, SF2523 was shown to have a synergistic effect with remdesivir or MU-UNMC.…”
mentioning
confidence: 93%